PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS ANEKDOT SISWA KELAS X SMA NEGERI 3 PAYAKUMBUH - Friska Putri Anisa Triane; Farel Olva Zuve (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research is titled “The Influence of Discovery Learning Model Assisted by Audiovisual Media on the Writing Skills of Anecdotal Texts in Class X Students of SMA Negeri 3 Payakumbuh.” The aims of this study are to describe the writing skills of students in anecdotal texts without and with the application of the discovery learning model assisted by audiovisual media, as well as to analyze its effects on writing skills. The method used is quantitative with a Control-only group posttest design. The research sample consists of 36 students divided into two groups: a control class and an experimental class. The findings indicate that the use of the discovery learning model assisted by audiovisual media significantly enhances students' writing skills in anecdotal texts. Additionally, this study finds that this learning model is more effective than conventional methods in improving students' creativity and understanding. This result is expected to contribute to the development of teaching methods in Indonesian language learning.